Design Concepts for Peel-Dominant Adhesive Joints in Aeronautic Applications - Lopes, J.P.M.; Campilho, R.D.S.G.; Bellali, M.A.; Baghdadi, M.C. (Journal of Research Updates in Polymer Science, 2023)
The adhesive bonding technique is employed from the aeronautical/aerospace industry to current house products. To comply with the requirements of distinct applications, different joint configurations are available to the designer. While single-lap joints (SLJ) are the most common in application and research, double-lap joints, scarf joints and T-joints find specific applications. T-joints are seldom studied in the literature, but these are used, for instance, in aircraft to bond the stiffener beams to the skin, or in the cars between the B-pillar and the rocker. Due to the high stress concentrations, T-joints often fail under average stresses much lower than the adhesive strengths, giving rise to the necessity for proper design and strength improvement methodologies. This work initially aims to validate the cohesive zone modelling (CZM) technique with experiments, and then use it to numerically evaluate and optimize the performance of T-joints subjected to peel loads. CZM is nowadays regarded as the most powerful strength prediction tool for adhesive joints, and can be a valuable tool to improve T-joints. Different features are addressed for a complete analysis: adhesive type, geometrical parameters, dual-adhesive technique for strength improvement, and composite joints. The evaluated geometrical parameters are the base adherend thickness (a), T-part thickness (t), overlap or bonding length (l) and curvature radius (r). As a result of this work, the model was successfully validated, and clear design guidelines were provided to define the ideal geometric and material (adhesive) conditions for best performance.